2022
DOI: 10.1007/s00018-021-04125-w
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cardiomyocyte-derived extracellular vesicles reflect cardiac injury during systemic inflammatory response syndrome in mice

Abstract: The release of extracellular vesicles (EVs) is increased under cellular stress and cardiomyocyte damaging conditions. However, whether the cardiomyocyte-derived EVs eventually reach the systemic circulation and whether their number in the bloodstream reflects cardiac injury, remains unknown. Wild type C57B/6 and conditional transgenic mice expressing green fluorescent protein (GFP) by cardiomyocytes were studied in lipopolysaccharide (LPS)-induced systemic inflammatory response syndrome (SIRS). EVs were separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…As such, this could ultimately limit the pathogenesis and the onset of misfolding associated disease mechanisms, and in perspective, represent a potential target to develop novel therapeutic intervention 70 . It may be interesting to identify the presence of these EVs in the circulating blood as previously demonstrated in cardiomyocyte-derived EVs, which were present in the circulation and reflecting cardiac injury that can serve as biomarker of cardiac injury 71 , 72 . The EVs protein cargo composition associated with proteostasis functions of the cardiomyocytes make them attractive potential biomarkers to detect cardiac health 73 .…”
Section: Discussionmentioning
confidence: 93%
“…As such, this could ultimately limit the pathogenesis and the onset of misfolding associated disease mechanisms, and in perspective, represent a potential target to develop novel therapeutic intervention 70 . It may be interesting to identify the presence of these EVs in the circulating blood as previously demonstrated in cardiomyocyte-derived EVs, which were present in the circulation and reflecting cardiac injury that can serve as biomarker of cardiac injury 71 , 72 . The EVs protein cargo composition associated with proteostasis functions of the cardiomyocytes make them attractive potential biomarkers to detect cardiac health 73 .…”
Section: Discussionmentioning
confidence: 93%
“…In the absence of active viral infection, the excess presence of MDVs in circulation has been recognized as a potential marker for the development of cardiovascular disease, particularly in patients with metabolic disorders, such as type 2 diabetes, insulin resistance, and atherosclerosis [ 130 ]. Similarly, increased amount of cardiomyocyte-derived extracellular vesicles and mitochondria was detected in circulation following cardiac injury [ 131 ]. A key step in MDV production is vesicle fragmentation/division from the mitochondrial network, which has been observed in several clinical settings, including DCM, congenital heart disease, and heart failure [ 132 ].…”
Section: Enterovirus-mitochondria Crossfirementioning
confidence: 99%
“…In contrast to healthy mt induced repair function, oxidatively damaged mt (whole or in part) can be exported in exosomes of injured CMC. A study by Hegyasi et al (2022) found that injured CMC preferentially secrete mt‐enriched LEVs which are detectable in circulation and represent diagnostic value. Although, little is known about the diagnostic utility of mt‐enREXO in cardio biology, few initial studies are indicative of its clinical predictive value especially during trauma or heart surgery where local cardiac vascular beds display a surge in mt‐DNA loaded plasma exosomes (Baysa et al, 2019).…”
Section: Implication Of Mt‐cargo In Cellular Signaling and As Biomarkermentioning
confidence: 99%